Seasonal variation in hyperparasitaemia and gametocyte carriage in patients with Plasmodium falciparum malaria on the Thai-Burmese border. - Nacher, M; Carrara, V; Ashley, E; Mcgready, R; Hutagalung, R; Nguen, J; Thwai, K; Looareesuwan, S; Nosten, F (2004)
Between January 2000 and December 2002 monthly rainfall was correlated with the proportion of patients with hyperparasitaemic Plasmodium falciparum malaria and with the proportion of patients with P. falciparum gametocytes. During the observation period 6953 cases of P. falciparum malaria were treated at the Shoklo Malaria Research Unit in Maela refugee camp on the Thai-Burmese border. Three hundred and seventy-five of these patients had >/=4% of parasitized red blood cells. Although there were more monthly malaria cases in the rainy season, rainfall was negatively correlated with the proportion of patients with hyperparasitaemia (Spearman's rho = -0.59, P < 0.001 ), and the proportion of gametocyte carriers among P. falciparum cases, (Spearman's rho = -0.39, P = 0.018). After controlling for age and the origin of the patient, the odds ratio for developing hyperparasitaemia during the dry season was 1.6 (95% CI 1.14-2.2; P = 0.006). The adjusted odds ratio for gametocyte carriage during the dry season was 1.3 (95% CI 1.03-1.6; P = 0.02). Migrations, changes in transmission patterns, the haematological burden of cumulative infections, and ultraviolet immunosuppression are discussed as potential explanations for these observations.